Modulating Patient Perception of Systemic Psoriasis Treatment Risk. Issue 3 (July 2019) - Seger, Edward W.; Unrue, Emily; Tablazon, Ingrid; Cline, Abigail; Cardwell, Leah A.; Richardson, Irma; Feldman, Steven R.
Background: Perception of medication risk is often disproportionately greater than actual risk. As a result, patients with psoriasis who would benefit from biologic therapies may be reluctant to start therapy, despite these medications' favorable safety profile. The purpose of this study is to determine whether perceptions of biologic medications change when reviewing a handout designed to portray risk use alongside common risks unrelated to medication use. Methods: A handout designed to put biologic medication risk into perspective was compared to 2 standard of care handouts on systemic and biologic medication for psoriasis. Twenty adult patients and 17 parents who have a child with moderate to severe psoriasis were randomized to receive each handout and complete a questionnaire related to perceived risk and willingness to use. The questionnaire assessed patient's likeliness of use, and comfort with use, and perceived risks associated with biologic medications. Statistical analysis was performed using t tests and Fisher exact test. Results: Patients reported a lower perceived risk with biologic medication use when using the newly designed handout (average score of 4.1 of 10 compared to 4.7 and 5.1 with current standard of care). Comfort with taking biologic medications was also higher with this handout compared to a 15-page standard of care handout ( P = .029). Limitations: This study was observational and contained a small sample size. Conclusions: Handouts specifically designed to portray risk of biologic medications for the treatment of psoriasis can reduce perceived risk and increase comfort with use as compared to the current standard of care.